2010
DOI: 10.1007/s12597-010-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics model for simulation of the dynamics of corneal transplants

Abstract: The increasing need for organ transplants demands the Hospital Management System (HMS) to face the future challenges of meeting such demands with effective policy decisions. This paper analyzes the various dynamics involved in corneal transplants by means of System Dynamics simulation and the waiting list of patients awaiting corneal transplants has been studied. The simulation model has is validated using actual data collected from a local hospital. Non-parametric statistical tests have been performed and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, there is no application example of systematic dynamic models in the context of liver transplantation. However, examples of kidney[ 37 ] and corneal[ 38 ] transplantation showed that the predicted number of transplantations are consistent with observed results, which indicates the potential usefulness of system dynamic models for this field.…”
Section: What Is Decision Modelling?supporting
confidence: 76%
“…To the best of our knowledge, there is no application example of systematic dynamic models in the context of liver transplantation. However, examples of kidney[ 37 ] and corneal[ 38 ] transplantation showed that the predicted number of transplantations are consistent with observed results, which indicates the potential usefulness of system dynamic models for this field.…”
Section: What Is Decision Modelling?supporting
confidence: 76%
“…In the education field, Pedamallu et al (2010) applied a system dynamics model to evaluate educational infrastructure based on the quality of primary school of a developing country. In health area, Devi et al (2010) studied system dynamics modeling for the waiting list of corneal transplants patients, and Al-Khatib et al suggested a more understandable and sophisticated simulation method for hospital waste management by using system dynamics model (2016). Aside from many areas, system dynamics models can be proposed about WEEE as well.…”
Section: Introductionmentioning
confidence: 99%